2020
DOI: 10.1039/c9gc02983d
|View full text |Cite
|
Sign up to set email alerts
|

Solvometallurgical process for extraction of copper from chalcopyrite and other sulfidic ore minerals

Abstract: Extraction of copper from sufidic ores, either by pyrometallurgy or hydrometallurgy, has various limitations. In this study, a solvometallurgical process for the extraction of copper from sulfidic ore minerals (chalcopyrite, bornite, chalcocite and digenite) was developed by using an organic lixiviant (FeCl 3 as oxidizing agent and ethylene glycol (EG) as organic solvent). All the studied copper sulfide minerals could be leached efficiently with a FeCl 3 -EG solution. Other lixiviant systems, namely CuCl 2 -EG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 58 publications
0
27
0
1
Order By: Relevance
“…The concentration of Fe(II) in the leachates was quantified using an Agilent Cary 6000i UV−vis−NIR spectrometer with 1,10-phenanthroline as a colorimetric agent. 19 The samples were prepared by mixing a certain volume of the leachate with 1 mL of 1,10phenanthroline solution (0.5 wt % in CH 3 CN) and 1 mL of buffer solution (1: 1 v/v of 5 mol L −1 NaOH and 6 mol L −1 CH 3 COOH, pH = 3.5). The mixture was then diluted with milliQ water to 10 mL.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of Fe(II) in the leachates was quantified using an Agilent Cary 6000i UV−vis−NIR spectrometer with 1,10-phenanthroline as a colorimetric agent. 19 The samples were prepared by mixing a certain volume of the leachate with 1 mL of 1,10phenanthroline solution (0.5 wt % in CH 3 CN) and 1 mL of buffer solution (1: 1 v/v of 5 mol L −1 NaOH and 6 mol L −1 CH 3 COOH, pH = 3.5). The mixture was then diluted with milliQ water to 10 mL.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…, uranium, rhenium, zirconium, and copper) in organic solvents ( i.e. , bromide–ethyl acetate, bromide–methanol, chlorine–FeCl 3 –dimethylformamide, and FeCl 3 –ethylene glycol). Recent work of our research group showed that different metals can be dissolved in trihalide ionic liquids, with the trichloride compounds as the most reactive ones. , Nakao et al studied the dissolution of noble metals using elemental halogens and halides dissolved in polar organic solvents . The quantitative recovery of palladium from spent catalytic converters can also be achieved using N , N′ -dimethylperhydrodiazepine-2,3-dithione diiodine .…”
Section: Introductionmentioning
confidence: 99%
“…28 Solvometallurgical routes produce less aqueous waste and are often more selective than hydrometallurgical processes. [28][29][30][31] Often used green solvents in solvometallurgy are deep-eutectic solvents (DESs). [32][33][34] DESs are low-melting mixtures with a melting point much lower than those of its individual components.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27] In addition, DESs enable precious metals to be oxidized at lower overpotentials, 28 and are thus preferred in leaching applications. [29][30][31][32] In this paper, the effects of solvent's physicochemical properties, such as metal speciation and mass transport, on the efficiency of the EDRR method were investigated in aqueous chloride solution and in deep eutectic mixture of choline chloride with ethylene glycol in 1 : 2 molar ratio (1 : 2 ChCl : EG). Moreover, the concentration of chloride ions in this DES is ca.…”
Section: Introductionmentioning
confidence: 99%